Exercise during pregnancy. A narrative review asking: what do we know?. Issue 21 (1st July 2015) - Barakat, Ruben; Perales, María; Garatachea, Nuria; Ruiz, Jonatan R; Lucia, Alejandro
Abstract : Although there is no consensus as to whether exercise is beneficial during pregnancy, most studies report it poses no risk to either the mother or the fetus, and many suggest it to be beneficial to both. This review, which examines the evidence available, also reveals the many differences in study design followed, the type of exercise undertaken and the variables measured, which make it difficult to compare results. Advances in our understanding of the effects of exercise during pregnancy might best be made by undertaking randomised clinical trials with standardised protocols. However, most of the studies examining the relationship between exercise and pregnancy report no complications on maternal or fetal well-being. This is also in line with recent review studies advising that the pregnant population without obstetric contraindications should be encouraged to exercise during pregnancy. Therefore, the results of the present review stimulate those responsible for the healthcare of the pregnant woman to recommend moderate exercise throughout pregnancy without risk to maternal and fetal health.